2018
DOI: 10.1111/dom.13172
|View full text |Cite
|
Sign up to set email alerts
|

Semaglutide, reduction in glycated haemoglobin and the risk of diabetic retinopathy

Abstract: AimsTo evaluate diabetic retinopathy (DR) data from across the SUSTAIN clinical trial programme.Materials and methodsThe SUSTAIN clinical trial programme evaluated the efficacy and safety of semaglutide, a glucagon‐like peptide‐1 analogue, for the treatment of type 2 diabetes (T2D). In SUSTAIN 6, a 2‐year, pre‐approval cardiovascular outcomes trial, semaglutide was associated with a significant increase in the risk of DR complications (DRC) vs placebo. DR data from across the SUSTAIN trials were evaluated, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
151
3
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(176 citation statements)
references
References 24 publications
(46 reference statements)
1
151
3
10
Order By: Relevance
“…Moreover, increased incidence of diabetic retinopathy complications in the SUSTAIN‐6 trial, compared to other semaglutide studies or to cardiovascular outcome trials of other GLP‐1 RAs, could be related to the considerably higher prevalence of baseline diabetic retinopathy complications among trial participants. Notably, in a post‐hoc analysis of the SUSTAIN‐6 trial, no difference in the incidence rate for diabetic retinopathy complications was found between semaglutide and placebo trial arms in patients without pre‐existing diabetic retinopathy . Finally, increased incidence of diabetic retinopathy‐related events in the semaglutide arm could also be associated with the profound and rapid improvement of glycaemic control …”
Section: Discussionmentioning
confidence: 98%
“…Moreover, increased incidence of diabetic retinopathy complications in the SUSTAIN‐6 trial, compared to other semaglutide studies or to cardiovascular outcome trials of other GLP‐1 RAs, could be related to the considerably higher prevalence of baseline diabetic retinopathy complications among trial participants. Notably, in a post‐hoc analysis of the SUSTAIN‐6 trial, no difference in the incidence rate for diabetic retinopathy complications was found between semaglutide and placebo trial arms in patients without pre‐existing diabetic retinopathy . Finally, increased incidence of diabetic retinopathy‐related events in the semaglutide arm could also be associated with the profound and rapid improvement of glycaemic control …”
Section: Discussionmentioning
confidence: 98%
“…A follow‐up mediation analysis of the EMPA‐Reg trial has further suggested that only a modest proportion (23%‐29%) of the overall cardiovascular benefit was attributable to glucose lowering . A further mediation analysis of the SUSTAIN 6 trial has also raised concerns regarding the magnitude and rapidity with which glucose levels are lowered given the unexpected increased risk of retinopathy reported . Indeed, this adverse effect was observed during the first 16 weeks of the trial among patients who had pre‐existing disease and poor glycaemic control .…”
Section: Discussionmentioning
confidence: 99%
“…A further mediation analysis of the SUSTAIN 6 trial has also raised concerns regarding the magnitude and rapidity with which glucose levels are lowered given the unexpected increased risk of retinopathy reported . Indeed, this adverse effect was observed during the first 16 weeks of the trial among patients who had pre‐existing disease and poor glycaemic control . These findings have fuelled debate and further research as to the probable mechanisms for benefits and risks of SGLT‐2 inhibitors and GLP‐1 agonists, including effects on weight, blood pressure, glomerulotubular feedback, plasma volume and ventricular loading, fuel metabolism, inflammation and endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…In the ACCORD BP study, in which 1263 patients with type 2 diabetes were randomized to intensive vs standard antihypertensive therapy, BP control had no effect on the rate of progression of DR (adjusted odds ratio, 1.23; 95% CI, 0.84‐1.79; P = 0.29) . There was also no reported effect of BP on DR complications in the SUSTAIN 6 trial …”
Section: The Pathophysiology Of Early Worsening: Mechanism Of Actionmentioning
confidence: 98%